The influence of food industry enterprises on the efficiency of city wastewater treatment - Nychyk, Oksana; Salavor, Oksana; Nikolaieva, Oksana (My University, 2020)
За останні 5 років у Києві сталося 8 великих аварій на каналізаційних колекторах великого діаметра, що призвело до обмеження водопостачання майже для третини столиці України терміном до трьох днів. Під час опитування виявилося, що підприємства та організації різних видів діяльності скидають аміачний азот, фосфати, жири, хлориди та завислі речовини в каналізаційну мережу, які є основними забруднювачами. Найчастіше правил скидання не дотримуються торгівельні комплекси, молочні підприємства, виробники пива, великі супермаркети. Недотримання цих правил призводить до порушення роботи каналізації мережі мікрорайонів міста, а також до зношення очисних споруд, що приймають стічні води (наприклад, Бортницька станція аерації).

Over the past 5 years, there have been 8 major accidents in largediameter sewage collectors in Kyiv, which has limited water supply to nearlya third of Ukraine’s capital for up to three days. During the survey, it turned out that enterprises and organizations of various activities dump ammonia nitrogen, phosphates, fats, chlorides and suspended substances into the sewerage network, which are the main pollutants. Most often the rules are not followed by shopping and entertainment complexes, dairy enterprises, beer producers, large permarkets. Failure to comply with these rules will result in disruption of sewerage networks of residential districts and districts of the city, as well as treatment facilities for wastewater treatment plants receiving sewage data (eg Bortnytska Aeration Station).
Keywords: кафедра екології та екоменеджменту; міські очисні споруди; стічні води харчових підприємств; waste water of food enterprises; city ​​sewage treatment plants